Enantioselective synthesis of bicyclo3.n.1alkanes by chiral phosphoric acid-catalyzed desymmetrizing Michael cyclizations - Burns, Alan R; Madec, Amaël G E; Low, Darryl W; Roy, Iain D; Lam, Hon Wai (Chemical science (Cambridge), 2015)
2,2-Disubstituted cyclic 1,3-diketones containing a tethered electron-deficient alkene undergo chiral phosphoric acid-catalyzed desymmetrizing Michael cyclizations to give bridged bicyclic products in high enantioselectivities. Both bicyclo[3.2.1]octanes and bicyclo[3.3.1]nonanes are accessible using this methodology.2,2-Disubstituted cyclic 1,3-diketones containing a tethered electron-deficient alkene undergo chiral phosphoric acid-catalyzed desymmetrizing Michael cyclizations to give bridged bicyclic products in high enantioselectivities. Both bicyclo[3.2.1]octanes and bicyclo[3.3.1]nonanes are accessible using this methodology.